Analysis Price and Promotion of Customer Loyalty in Modern Retail Shopping Centers in The Pandemic Time Covid-19 Through The Purchase Decision Strategy as Moderation - Alya Zulfa Cahyani; Elvina; Agus Rahmat Hermawanto; Novrihan Leily Nasution (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This study aims to determine how much influence there is in terms of price, promotion, and customer loyalty through the strategy of consumer purchasing decisions as moderation, this research is very important in finding a marketing strategy solution for modern retail shopping centers in PANDEMIC COVID-19 conditions. This research uses quantitative methods with a sample of 258 SME companies using SEM analysis Amos 23. The results of the study strengthen the significant influence of price strategy and promotion of modern retail shopping centers on customer loyalty with purchasing decisions as moderation. This research is an evaluation of the shopping center marketing strategy in modern retail to carry out a strategy to survive in the COVID-19 PANDEMIC. The results show that the application of price and promotion of modern retail shopping centers to customer loyalty with purchasing decisions as moderation is very significant. We discuss the implications of these findings to be able to save modern retailers, which are currently not operating, the advice is given as soon as possible by modern retailers to improve their marketing methods by increasing competitive prices, proper promotion by giving attractive discounts to keep consumers loyalty. Keywords: customer loyalty, price, promotions, purchase decisions.